SIMULATION OF LAMINAR FORCED CONVECTION HEAT TRANSFER AND FLUID FLOW OVER A BACKWARD FACING STEP WITH OBSTACLE USING (SIO ) NANOPARTICLES (University of Thi-Qar Journal for Engineering Sciences, 2015)
Simulation of Heat transfer and laminar Sio2/water and Sio2/oil-engine flow over backward facing step with and without obstacle numerically studied in this paper. The finite volume method adopted to solve continuity,momentum and energy equations in two dimensions. The aspect ratio of triangular obstaclew/e= 0.5 presented.The step height and expansion ratio of channel were 4.8mm and 2 respectively, the range of Reynolds number varied from 100 to 250, constant heat flux subjected on downstream of wall was 2000W/m2.Two types of base fluid used in this simulation the water and oil-engine with constant properties at T = 300K°, The Sio2nanoparticles used with nanoparticles diameter 30nm and volume friction 4%. The average nusselt number noticed increase with increase Reynolds number withobstaclefor two basefluid and also noticed that the nanofluid of Sio2-oil engine has higher nusselt number compared with other nonofluid. The result shows increase of local nusselt numberfor backward facing step with obstacle in compared to those without obstacle. The maximum enhancement of heat transfer observed at obstacle due to increase recirculation flow after the obstacle. Streamline showing the increase of recirculation region with used obstacle in compared without obstacle and highest recirculation region observed at obstacle.